PENGARUH SUMBER DAYA INSANI TERHADAP KINERJA KARYAWAN PERBANKAN SYARIAH (Studi Kasus Bank Pengkreditan Rakyat Syariah Adeco Langsa) - febi febi; Muhammad Dayyan; Ade Fadillah FW Pospos; Iqbal Ilham (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2019)
The success of a bank is determined by the performance of its employees, employee performance is an important indicator in improving the quality of sharia banking. Employee performance is influenced by many factors such as the quality of human resources. The purpose of this research is To know whether there is influence between human resources but performance of Adebo BPRS employee, To know how big influence of human resource to performance of employees of Adeco BPRS, and last To know how Adeco BPRS increase source human resources of employees in improving company performance. The method used in this research is survey method with quantitative approach. The population in this research is all employees of Adeco BPRS with sample is 20 customer. The results obtained in this study indicate that there is a significant positive effect between human resources on employee performance in Adeco BPRS. From the result of SPSS test, it is known that human resources have 36% effect on employee performance on Adeco BPRS, while 64% is influenced by other variable which is not examined in this research. In improving employee performance, Adeco BPRS has made SOPs on the rights and obligations that must be fulfilled by each employee, not only that employees are also given regular training both internal training and external training. Adeco BPRS also makes a policy that for employees who excel will be rewarded in the form of bonuses, additional salary and promotion / position. While employees who perform poorly will be given Phunisment (sanctions) namely the decline of office and dismissal.